2022
DOI: 10.1186/s40779-022-00409-9
|View full text |Cite
|
Sign up to set email alerts
|

An integrated microfluidics platform with high-throughput single-cell cloning array and concentration gradient generator for efficient cancer drug effect screening

Abstract: Background Tumor cell heterogeneity mediated drug resistance has been recognized as the stumbling block of cancer treatment. Elucidating the cytotoxicity of anticancer drugs at single-cell level in a high-throughput way is thus of great value for developing precision therapy. However, current techniques suffer from limitations in dynamically characterizing the responses of thousands of single cells or cell clones presented to multiple drug conditions. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…Taking advantage of microfluidics, it was possible to separate single cells and promote the formation of single-cell-derived colonies for drug testing. An array with more than 4000 microchambers coupled to a concentration gradient generator allowed researchers to distinguish cell heterogeneity of both a leukemia cell line and primary tumor cells [ 30 ]. The device enables researchers to monitor cell viability over several time points by registering the fluorescence of live and dead cells.…”
Section: Fluorescence-based Biosensorsmentioning
confidence: 99%
“…Taking advantage of microfluidics, it was possible to separate single cells and promote the formation of single-cell-derived colonies for drug testing. An array with more than 4000 microchambers coupled to a concentration gradient generator allowed researchers to distinguish cell heterogeneity of both a leukemia cell line and primary tumor cells [ 30 ]. The device enables researchers to monitor cell viability over several time points by registering the fluorescence of live and dead cells.…”
Section: Fluorescence-based Biosensorsmentioning
confidence: 99%
“…168 Remarkably, Ooc technology could simulate the concentration gradient distribution of drugs in the body through a drug gradient concentration control system to assess the toxicity and effects of drugs at different concentrations. 169,170 For example, Grant and colleagues developed a PDMS organ chip containing two parallel channels separated by a porous membrane arranged by living cells and described a combined experimental and computational strategy to estimate changes in drug concentration over time without prior knowledge of the partition or diffusion coefficients. The application of this strategy not only increases the usefulness of organoids in clinical research projects, but also allows their application to other forms of drug testing.…”
Section: Ooc Technology For Drug Discoverymentioning
confidence: 99%
“…On the one hand, some cellular biological responses are dependent on specific biomolecular concentrations and thus the control of drug concentration gradients is of great significance in drug toxicity screening 168 . Remarkably, Ooc technology could simulate the concentration gradient distribution of drugs in the body through a drug gradient concentration control system to assess the toxicity and effects of drugs at different concentrations 169,170 . For example, Grant and colleagues developed a PDMS organ chip containing two parallel channels separated by a porous membrane arranged by living cells and described a combined experimental and computational strategy to estimate changes in drug concentration over time without prior knowledge of the partition or diffusion coefficients.…”
Section: Application Of Ooc In Cardiovascular Disease Researchmentioning
confidence: 99%
“…Overcoming the challenge of increasing the sensitivity and specificity of microfluidic technology with regard to the screening and detection of key biomarkers of HNC requires a large testing sample population to reliably translate these techniques into a clinical setting [141]. High-throughput screening (HTS) is a technique that works by testing and analyzing large numbers of chemical or biological compounds against specific targets in a very short time, with the goal to develop either drug or diagnostic tools [142,143]. Researchers have observed that many limitations of existing HTP screening systems can be resolved by using microfluidic technologies since they can be produced at a much lower cost and work on liquid volumes at the level of nano-to microliters or smaller [143].…”
Section: Microfluidic Systems For Hnc Diagnosis and Screeningmentioning
confidence: 99%